Accountability And Transparency Impact on Muzzaki’s Willingness To Pay Zakat Through Zakat Institutions - Fitriningrum, Andriati; Deitiana, Tita; Rachbini, Widarto; Wijayaningrat, Mustikaratu (Dinasti Publisher, 2024)
This paper examines how zakat management’s accountability and transparency affect the muzzaki’s willingness to pay their zakat to a zakat management institution. The study was motivated by the crucial role of zakat in Muslim countries as a potential resource for improving their socio-economy. However, accountability and transparency of zakat institutions have failed of expectations. Muzzaki tend to give their zakat through mosques or non-profit organisations where less accountability and transparency. Prosocial behaviour theory which emphasises voluntary action to help others is selected. Meanwhile, mixed methods focusing on qualitative to facilitate quantitative methods are selected through Interview and distributing questionnaires to Muslims in the Bandung-Indonesia. 300 questionnaires were analysed using the PLS-SEM tools. This study reveals being transparent from the zakat management institution is control but when it comes to muzzaki behaviour, intention and choice to pay zakat as a voluntary expression of solidarity, it is made through official channels.